A new species of Pseudione Kossmann, 1881 (Isopoda, Cymothoida, Bopyridae) parasitizing the lobster Nephropsis aculeata Smith, 1881 (Decapoda, Astacidea, Nephropidae) in the Southwestern Atlantic - Horch, Amanda Porciuncula; Huber, Augusto Frederico; Araujo, Paula Beatriz; Ribeiro, Felipe Bezerra (Zootaxa, 2018)
A new species of Pseudione Kossmann, 1881 is described from two parasitized specimens of the clawed lobster Nephropsis aculeata Smith, 1881, collected from Brazilian waters in the southwestern Atlantic. It is the second species of the genus from Brazil and is the fourth species parasitizing nephropid lobsters in the world.